Pengaruh Return on Asset dan Current Ratio terhadap Return on Equity PT Astra International Tbk Periode 2018-2025: The Effect of Return on Asset and Current Ratio on Return on Equity of PT Astra International Tbk for the 2018-2025 Period - Iissya Handayani; Mareta Eka Sheillani; Nabila Aulia Safitri; Nabilla Fitriani; Hana Hartasya (PT Cakrawarti Empat Proksi, 2026)
Post pandemic economic dynamics make ROA and CR management crucial in maintaining the stability of the company's ROE. This study aims to analyze and test the influence of Return on Asset (ROA) and Current Ratio (CR) on Return on Equity (ROE) in PT Astra International Tbk for the 2018-2025 period. Using a causal quantitative approach, secondary data is obtained from the official quarterly financial statements from the Indonesia Stock Exchange Website and the company's website. The sampling technique using purposive sampling produced 32 quarterly data. Data analysis used classical assumption tests and multiple linear regression using SPSS software. The results of the partial test showed that ROA had a significant positive effect, while CR had a significant negative effect on ROE. Simultaneously, the two variables had a very strong significant effect in explaining the variation in ROE of 99.2%. Improving asset efficiency and optimal liquidity management are important factors to increase equity returns, as well as being the basis for management in developing profitability strategies. The implication of this study emphasizes that the management of PT Astra International Tbk needs to prioritize asset efficiency to boost profits, as well as control current assets so that there is no idle cash that reduces the effectiveness of capital return for shareholders.